Inhibition of hepatic p63 ameliorates steatohepatitis with fibrosis in mice - Marcos F. Fondevila; Eva Novoa; Uxia Fernandez; Valentina Dorta; Tamara Parracho; Henriette Kreimeyer; Maria Garcia-Vence; Maria P. Chantada-Vazquez; Susana B. Bravo; Begoña Porteiro; Alba Cabaleiro; Mijra Koning; et al. (Elsevier, 2024)
Objective: p63 is a transcription factor involved in multiple biological functions. In the liver, the TAp63 isoform induces lipid accumulation in hepatocytes. However, the role of liver TAp63 in the progression of metabolic dysfunction-associated steatohepatitis (MASH) with fibrosis is unknown. Methods: We evaluated the hepatic p63 levels in different mouse models of steatohepatitis with fibrosis induced by diet. Next, we used virogenetic approaches to manipulate the expression of TAp63 in adult mice under diet-induced steatohepatitis with fibrosis and characterized the disease condition. Finally, we performed proteomics analysis in mice with overexpression and knockdown of hepatic TAp63. Results: Levels of TAp63, but not of ΔN isoform, are increased in the liver of mice with diet-induced steatohepatitis with fibrosis. Both preventive and interventional strategies for the knockdown of hepatic TAp63 significantly ameliorated diet-induced steatohepatitis with fibrosis in mice fed a methionine- and choline-deficient diet (MCDD) and choline deficient and high fat diet (CDHFD). The overexpression of hepatic TAp63 in mice aggravated the liver condition in mice fed a CDHFD. Proteomic analysis in the liver of these mice revealed alteration in multiple proteins and pathways, such as oxidative phosphorylation, antioxidant activity, peroxisome function and LDL clearance. Conclusions: These results indicate that liver TAp63 plays a critical role in the progression of diet-induced steatohepatitis with fibrosis, and its inhibition ameliorates the disease.